2021
DOI: 10.22141/2224-1507.7.3.2017.116863
|View full text |Cite
|
Sign up to set email alerts
|

Молекулярно-Клітинні Механізми Захисної Дії Вітаміну D3 При Експериментальному Преднізолон-Індукованому Остеопорозі

Abstract: Актуальність. Довготривале введення глюкокортикоїдів (ГК) супроводжується порушенням мінерального обміну і, як наслідок, призводить до розвитку вторинного остеопорозу. Важливу роль у регулюванні процесу ремоделювання кісткової тканини відіграє вітамін D, який може реалізовувати свої біо­логічні ефекти через рецептор вітаміну D — VDR-опосередкований вплив на цитокінові системи, зокрема RANKL-RANK-OPG (ліганд рецептора активатора ядерного фактора транскрипції NF-κB — рецептор RANKL — остеопротегерин). Мета. Досл… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
3
0
0
Order By: Relevance
“…As for osteoclastogenesis, available scientific data indicate that both the decrease and increase in this process can account for the bone loss, provided that there is a concomitant decline in the formation and functional ability of osteoblasts ( 33 , 34 ). Several recent studies which largely correspond to experimental design of the present investigation has demonstrated that chronic exposure of high GC doses had inhibiting effects both on bone formation and bone resorption ( 35 , 36 ). The discrepancy between prednisolone-induced osteoclastogenic profiles of cytokines, the increase in the number of circulating RANK-positive cells, and the low bone turnover can be explained by suppressed recruitment of OCPs from the BM to the bones.…”
Section: Discussionsupporting
confidence: 53%
“…As for osteoclastogenesis, available scientific data indicate that both the decrease and increase in this process can account for the bone loss, provided that there is a concomitant decline in the formation and functional ability of osteoblasts ( 33 , 34 ). Several recent studies which largely correspond to experimental design of the present investigation has demonstrated that chronic exposure of high GC doses had inhibiting effects both on bone formation and bone resorption ( 35 , 36 ). The discrepancy between prednisolone-induced osteoclastogenic profiles of cytokines, the increase in the number of circulating RANK-positive cells, and the low bone turnover can be explained by suppressed recruitment of OCPs from the BM to the bones.…”
Section: Discussionsupporting
confidence: 53%
“…We established that prednisolone administration caused a decrease in Vdr mRNA level by 1.37-fold that may contribute to antiosteoblastic effects of GC ( Figure 2(a) ). This is consistent with the previous results indicating lower VDR protein level in bone tissue after prednisolone load [ 23 ]. Reduced VDR level in bone tissue may be attributable to a possible decrease in cell responsiveness to vitamin D action and, as a result, impaired local auto-/paracrine regulation of cell function by vitamin D. At the same time, a 1.71-fold increase in the expression of Cyp27b1 mRNA in bone tissue was shown ( Figure 2(b) ), which suggests a compensatory response to lower levels of the components of the vitamin D auto-/paracrine system, 25(OH)D and VDR.…”
Section: Resultssupporting
confidence: 94%
“…Immunofluorescence staining of rat femur sections with anti-RANK-antibody showed the lowering of RANK level in prednisolone-administered rats ( Figure 4 ). These data are in agreement with our previous results that revealed a decrease in the protein level of RANK in bone tissue [ 23 ]. Moreover, the study on BALB/c male mice demonstrated that the number of osteoclasts in the areas of bone destruction was significantly decreased in the GC-treated animals compared with the control group [ 30 ].…”
Section: Resultssupporting
confidence: 94%